Mathematical Disposition of Students in Open-Ended Learning Based on Ethnomathematics - Ulya, Himmatul; Rahayu, Ratri (Journal of Education Technology, 2021)
Students' low disposition in mathematics causes students to view mathematics as difficult to understand, thus affecting mathematics learning outcomes. Not many students are active because they lack self-confidence, interest in learning mathematics, and curiosity about mathematics. This has an impact on low mathematics learning outcomes. This study aims to test the increase in the mathematical disposition of students who take part in open-ended learning based on ethnomathematics and determine the effect of mathematical disposition on students' mathematical abilities. This quantitative study refers to a one-group pretest-posttest design. Data collection techniques in this study used non-test and test techniques. The instruments used are questionnaires to measure students' mathematical dispositions and test questions to measure students' mathematical abilities. Data analysis techniques used are gain test and regression analysis. The results study indicates that the mathematical disposition of students who participate in open-ended learning based on ethnomathematics increased by 47%, which means that they are in the medium category and mathematical dispositions affect students' mathematical abilities through the application of open-ended questions learning based on ethnomathematics by 57.9%. It is concluded that ethnomathematics-based open-ended learning can improve students' mathematical disposition. This research is that teachers can use open-ended learning based on ethnomathematics to improve students' mathematical dispositions.